Queer Tolstoy A Psychobiography - Sethness Castro, Javier (Taylor & Francis, 2023)
Queer Tolstoy is a multidimensional work combining psychanalysis, political history, LOGBTQ+ studies, sexology, ethics, and theology to explore the life and art of Count Lev Nikolaevich Tolstoy. Using a psychobiographical framework, Sethness Castro uncovers profoundly queer dimensions in Tolstoy's life experiences and art. Deftly contributing to the progressive and radical analysis of gender and sexuality, this book examines how Tolstoy's erotic dissidence informed his anarchist politics, anti-militarist ideas, and voluminous literary production. Sethness Castro analyzes the influence of Buddha, Socrates, Jesus, Cervantes, Rousseau, Kant, Herzen, Proudhon, Chemyshevsky, and his mother Marya Volkonskyaya on the artist's writings. Furthermore, he details Tolstoy's emblematic linking of LGBTQ+ desire with moral and erotic self-determination and resistance to Tsarist despotism-especially in War and Peace. This book is vital reading for those interested in the intersection of literature, psychoanalysis, queer studies, and Russian history.